2021
DOI: 10.1111/mec.16210
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and predictive phylogeography in the South American diagonal of open formations: Unravelling the biological and environmental influences on multitaxon demography

Abstract: Phylogeography investigates historical drivers of the geographical distribution of intraspecific lineages. Particular attention has been given to ecological, climatic and geological processes in the diversification of the Neotropical biota. Several species sampled across the South American diagonal of open formations (DOF), comprising the Caatinga, Cerrado and Chaco biomes, experienced range shifts coincident with Quaternary climatic changes. However, comparative studies across different spatial, temporal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…Our results support an ancient divergence between two well-defined lineages (NE and SW) for N. kemneri, which occurred during the Plio-Pleistocene transition, reinforcing the role of climatic and vegetation variation events in the diversification of the DOF biota (Del'Arco and Bezerra, 1989;Wang et al, 2004). Further climatic fluctuations during the Quaternary had pronounced effects on the Caatinga biota (Bonatelli et al, 2021) and could have facilitated the expansion and diversification of N. kemneri across the NE region of the DOF, while refugia zones in the Southeastern region may account for the constricted diversity patterns within the Cerrado, and altogether explain the unique evolutionary history of these two separate populations. The findings presented in this work, however, came from a few mitochondrial markers, and the investigation using multi-locus nuclear data can reveal other relevant patterns in the population genetic structure in this species.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results support an ancient divergence between two well-defined lineages (NE and SW) for N. kemneri, which occurred during the Plio-Pleistocene transition, reinforcing the role of climatic and vegetation variation events in the diversification of the DOF biota (Del'Arco and Bezerra, 1989;Wang et al, 2004). Further climatic fluctuations during the Quaternary had pronounced effects on the Caatinga biota (Bonatelli et al, 2021) and could have facilitated the expansion and diversification of N. kemneri across the NE region of the DOF, while refugia zones in the Southeastern region may account for the constricted diversity patterns within the Cerrado, and altogether explain the unique evolutionary history of these two separate populations. The findings presented in this work, however, came from a few mitochondrial markers, and the investigation using multi-locus nuclear data can reveal other relevant patterns in the population genetic structure in this species.…”
Section: Discussionsupporting
confidence: 78%
“…The depressions inhibited gene flow between east and west of the plateau, and promoted diversification of subsequently isolated populations of flora and fauna. As discussed by Bonatelli et al (2021), while several species across the DOF experienced range shifts, there is no single demographic response to Pleistocene climatic fluctuations. Some species experimented demographic expansion, others exhibited the opposite response, and some, like N. kemneri, underwent different processes since the separation of both populations (i.e., 59), where each experienced different evolutionary histories, illustrated by the different structures displayed by the haplotype network.…”
Section: Discussionmentioning
confidence: 99%
“…From the retrieved results, we selected papers where the authors explicitly pointed out that their species are endemic to the campos rupestres, the main vegetation of the BQM. We selected only mitochondrial and/or plastidial sequences as the main molecular markers, excluding other techniques (e.g., RAPD, allozymes, SSR), to homogenize the substitution rates across lineages, a desirable condition for the subsequent hABC demographic analyses (Bonatelli et al, 2022). We also excluded papers that did not explicitly include the accession numbers of the deposited sequences, as well as those papers with less than 10 individuals Plastidial and mitochondrial data were downloaded from Genbank for each species (see Appendix S2 for accession numbers).…”
Section: Data Processingmentioning
confidence: 99%
“…Climatic changes during the Quaternary promoted complex phylogeographic patterns in many southern South American arthropods, such as the grasshopper Dichroplus vittatus Bruner (Rosetti et al, 2022), the beetle Naupactus cervinus Boheman (Rodriguero et al, 2016), mygalomorph spiders (Calatayud-Mascarell et al, 2022, among other taxa (Bonatelli, Gehara, Carstens, Colli & Moraes, 2022). Similar phylogeographic consequences of climate change over the last 21,000 years have been recently documented for O. bonaerensis , one of the host species for C. cactorum (Köhler, Esser, Font, Souza-Chies & Majure, 2020).…”
Section: East and South (Pampean) Lineages Divergencementioning
confidence: 99%
“…Linear regression analyses revealed that population genetic diversity was significantly correlated with habitat stability. The Chaco region, representing the northernmost distribution limits of C. cactorum , is an open vegetation biome characterized by high endemicity and diversity for both plant and animal species (Bonatelli et al, 2022;Brusquetti, Netto, Baldo, & Haddad, 2019;Nores, 1994;Werneck, 2011). Analyses of environmental habitat suitability between the present and the LGM revealed relative habitat stability within the Chaco (Figure 4).…”
Section: Climatic Stability and Patterns Of Genomic Diversitymentioning
confidence: 99%